Association of interferongamma release assay and SARS-CoV-2 reverse transcriptase polymerase chain reaction test results in adults tested in a tertiary medical center - Evelina N Lagamayo; Grace C King; Ma Concepcion Osano (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2021)
Introduction: For a country with high Tuberculosis (TB) prevalence, infection of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus with a covert co-infection of Mycobacterium Tuberculosis (MTB) is a real concern. The two pathogens being both intracellular infectious agents, share a common initial host immune response of innate immunity activation, signalling cascade of inflammatory cytokines and chemokines, and eventual adaptive immunity activation in order to remove and/or neutralize the microbes. Interferon-Gamma Release Assay (IGRA) is a TB diagnostic tool that indirectly tests for Latent TB Infection (LTBI) by measuring the interferongamma released by T cells in response against MTB-specific antigens. This study was conducted to determine if the T cell response to IGRA will be affected by the host immune response to coronavirus disease-19 (COVID-19) caused by SARS-CoV-2 virus. objective: The study intended to determine if there was an association between the IGRA results and COVID-19 confirmed patients based on their overlapping immunopathophysiology. Methodology: This was an analytic, cross-sectional study encompassing the two-month enhanced community lockdown in the National Capital Region (NCR) from March 10, 2020 to May 12, 2020. The investigator accessed both the records of IGRA test results with corresponding records of SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) test results during the selected study period. Designated code served as patient identifier to protect patient privacy and confidentiality. Results: The 37 patients included in the study were all adult, mostly in 60-69 age range (mean age 57.5 years) with a slight male predominance (57%). The total detected SARS-CoV-2 cases were 62.2%, whereas the positive IGRA results were 16%. IGRA and SARS-CoV RT-PCR test results have statistically significant association. Majority of COVID-19 confirmed patients exhibited an indeterminate IGRA test result. Conclusion: IGRA result, being an immune response-dependent test, was susceptible to an on-going SARS-CoV-2 infection due to the similarity of natural host immune response to both MTB and SARS-CoV-2.